2007
DOI: 10.12968/denu.2007.34.9.556
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries – A Review

Abstract: Currently, some 4 out of 10 children starting school have decay in their primary dentition. It is prudent for dentists who diagnose ECC to provide therapy or, if treatment is not possible as a result of the young age of the child and limited co-operation, then it is important to refer the patient to an appropriately trained individual for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 0 publications
1
28
1
11
Order By: Relevance
“…Dental caries is the most common chronic disease of the oral cavity, which affects the population in general, from children to adults and seniors (1,2). Several epidemiological population-based studies have demonstrated a significant decrease in caries worldwide, a fact that is not demonstrated when the object of the study are preschool children (3).…”
Section: Introdutionmentioning
confidence: 99%
“…Dental caries is the most common chronic disease of the oral cavity, which affects the population in general, from children to adults and seniors (1,2). Several epidemiological population-based studies have demonstrated a significant decrease in caries worldwide, a fact that is not demonstrated when the object of the study are preschool children (3).…”
Section: Introdutionmentioning
confidence: 99%
“…Night after night, repeated bathing of a young child's teeth in these acid-promoting substances leads to rampant decay. 58 The primary DOI:10.1002/MSJ maxillary incisors and mandibular molars are directly subjected to the sugary liquids; consequently, they are the teeth that are most commonly affected by this decaying process (Figure 4). Interestingly, the child's tongue tends to protect the mandibular incisors from the liquid emanating from the bottle's nipple, which is positioned between the tongue and the palate.…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…an integral approach Estela M. Losso, 1 Maria Cristina R. Tavares, 2 Juliana Y. B. da Silva, 3 Cícero de A.…”
Section: Recent Studies Carried Out In Brazil Have Demonstratedmentioning
confidence: 99%
“…1,2 An important factor that must be considered is the fact that it can be prevented, controlled or even resolved.…”
Section: Introductionmentioning
confidence: 99%